Oral Cavity Microbiome Impact on Respiratory Infections Among Children - Crestez AM; Nechita A; Daineanu MP; Busila C; Tatu AL; Ionescu MA; Martinez JD; Debita M (Dove Medical Press, 2024)
Alexandra Mihaela Crestez,1,2 Aurel Nechita,1,2 Miruna Patricia Daineanu,1,2 Camelia Busila,1,2 Alin Laurentiu Tatu,2- 4,* Marius Anton Ionescu,5 Jose Dario Martinez,6,* Mihaela Debita7,8 1Pediatric Department, "Sf. Ioan" Emergency Clinical Pediatric Hospital, Galați, 800494, România; 2Clinical Medical Department, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, 800201, România; 3Dermatology Department, "Sfanta Cuvioasa Parascheva" Hospital of Infectious Diseases, Galați, 800179, România; 4Multidisciplinary Integrated Center of Dermatological Interface Research MIC-DIR "Dunărea de Jos" University, Galați, 800201, România; 5Department of Dermatology, University Hospital Saint Louis, Paris, 75475, France; 6Department of Internal Medicine, Faculty of Medicine, University Autonomous of Nuevo León, Monterrey, 66455, Mexico; 7Department of Infectious Disease, "Sfanta Cuvioasa Parascheva" Hospital of Infectious Diseases, Galați, 800179, România; 8Clinical Department, Faculty of Medicine and Pharmacy, "Dunărea de Jos" University, Galați, 800201, România*These authors contributed equally to this workCorrespondence: Camelia Busila; Miruna Patricia Daineanu, Email camelia_busila@yahoo.com; miruna.dragostin@yahoo.comBackground: The respiratory system, traditionally considered antiseptic, harbors a diverse and dynamic bacterial microbiome. Recent advancements in microbiome research have revealed its significant influence on both innate and adaptive immunity, particularly in the context of respiratory infections in children. This article also provides an overview of the types of bacteria that commonly affect the respiratory system, including Streptococcus pneumoniae, Moraxella catarrhalis and Haemophilus influenzae. These bacteria are prevalent in pediatric populations and significantly contribute to the development and severity of respiratory tract infections (RTIs).Purpose: This review aims to evaluate the impact of the oral cavity and upper respiratory microbiome on the susceptibility and severity of respiratory infections in pediatric populations. We specifically focus on how early colonization patterns of bacteria such as Moraxella and Streptococcus contribute to the development of respiratory tract infections in children from birth through adolescence.Methods: A thorough literature review was performed, focusing on studies publishing between 2004 and 2023. The review included research exploring the role of the upper respiratory microbiome in pediatric populations, with a specific focus on children aged birth to 18 years. Emphasis was placed on microbial characterization, the modulation of immune responses in respiratory tract infections, and the potential therapeutic applications of microbiome-targeted interventions.Results: The findings suggest that the composition and disruption of the upper respiratory microbiome significantly influence clinical outcomes in children with respiratory infections. Notably, dysbiosis in the microbiome has been linked to increased susceptibility to repeated infections, highlighting the importance of maintaining microbial balance for optimal respiratory health.Conclusion: Understanding the impact of oral cavity and upper respiratory microbiome could lead to improved management and prevention strategies for respiratory infections in children. This review underscores the potential of microbiome modulation, including the use of probiotics as a therapeutic approach to enhance clinical outcomes in pediatric respiratory infections.Keywords: microbiome, children, immunity, respiratory infections